2021
DOI: 10.1111/ntwe.12190
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguous workarounds in policy piloting in the NHS: Tensions, trade‐offs and legacies of organisational change projects

Abstract: Pilot projects are increasingly used as a mechanism to enact organisational change, particularly government policy. Information technology's centrality to organisations often makes it key to the introduction of new processes. However, it can give rise to workarounds as employees circumvent impediments it presents by rejecting its prescribed use. Workarounds tend to be conceptualised dichotomously, as either ‘good’ problem solving, or ‘bad’ subversion of the technology. In pilot projects, workarounds are more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
(109 reference statements)
0
6
0
Order By: Relevance
“…Yet, contemporary examples such as healthcare or education in the United Kingdom, Australia, and elsewhere, suggest that senior management will more likely find ways to mobilise the systems so that value can be extracted from professional work, ultimately straining but not breaking the psychological contract (Spina et al, 2020). Conflicts between organisational and social imperatives end up being contained or worked around within a professional ethos (Bailey et al, 2019; Goff et al, 2021), or are met with entrepreneurial zeal (Bailey et al, 2017; Hodgson et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, contemporary examples such as healthcare or education in the United Kingdom, Australia, and elsewhere, suggest that senior management will more likely find ways to mobilise the systems so that value can be extracted from professional work, ultimately straining but not breaking the psychological contract (Spina et al, 2020). Conflicts between organisational and social imperatives end up being contained or worked around within a professional ethos (Bailey et al, 2019; Goff et al, 2021), or are met with entrepreneurial zeal (Bailey et al, 2017; Hodgson et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…If they ‘spend less’ and thus generate a time‐counted profit, they are rewarded. If professional ‘workarounds’ are to be achieved (Dupret, 2017; Goff et al, 2021), labour must locate capacity for profitmaking as the relations between the social and the technical shift.…”
Section: Vignette 1: ‘Care’ In a Uk Social Care Organisation As Repos...mentioning
confidence: 99%
“…We have noted the effects of this within our case. Connected to the issue of time is the instrumental rationality that projects impose on their protagonists; that is, the need for measurable outcomes mobilises a search not for what might or could work, or work most effectively, but what can be made to work within the time available (Bailey et al, 2017; Bailey et al, 2019; Goff et al, 2021). This links to the self-referential nature of success noted above and may be somewhat more modest than the claims made during the tendering stage to meet the expectations for a successful application.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) found that informal practices negatively impacted operational performance, while Nasarwanji et al. (2016) and Goff et al. (2021) concluded that informal practices added unnecessary complexity.…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…The next hypothesis addresses the role of informal resilience in the operational performance of LPSs. Tucker et al (2020) found that informal practices negatively impacted operational performance, while Nasarwanji et al (2016) and Goff et al (2021) concluded that informal practices added unnecessary complexity. Moreover, informal practices may hinder the credibility of formal management structures, which may be interpreted as wasteful bureaucracy (Dekker, 2014).…”
Section: Jmtm 336mentioning
confidence: 99%